Rectangular copper nanotubes. Issue 130 (21st December 2015) - Chang, Yu-Hsu; Hsu, Ya-Ting; Tsai, Yu-Heng; Lai, Yi-Ru; Huang, Ting-Kai; Chiu, Hsin-Tien
Abstract : A straightforward galvanic displacement reaction was adopted to synthesize structurally novel rectangular Cu nanotubes. This 1D nanomaterial displayed excellent field emission properties and a favorable catalytic effect in the degradation of methylene blue in H2 O2 solutions. Abstract : One-dimensional Cu nanomaterials with a new morphology, rectangular copper nanotubes (copper NTs), were synthesized on a large-scale using a cetyltrimethylammonium chloride-assisted galvanic replacement reaction on rough Al substrates. In an acidic environment, Cu(ii ) is reduced on sharp-topped Al substrates and copper NTs 150–300 nm in diameter and 2–10 μm in length were formed through fine-tuning the reaction temperature and chemical stoichiometry. Field-emission measurement results show that the copper NTs emitting electrons at turn-on fields of 8.76 V μm −1 was observed with a field enhancement factor of 85. The superior catalytic property of copper NTs in the degradation of a methylene blue aqueous solution in the presence of H2 O2 was also presented in this article.